MANAGERIAL COMPETENCY OF MADRASAH PRINCIPAL IN DEVELOPING TEACHER MOTIVATION AT MAS PAB-2 HELVETIA - Muhammad Yasin (Hijri, 2020)
This study aims to describe the application of managerial competence in madrasah principals in the context of building teacher work motivation in MAS PAB-2 Helvetia. This research uses a qualitative approach. Data collected through observation, interviews, and documentation. The object of research is the headmaster of the madrasah of teachers and staff employees at MAS PAB 2 Helvetia. Based on the research analysis, the following data are obtained: (1) The madrasah head is not fully able to implement his managerial competence maximally. (2) The madrasah head always tries to approach and create a harmonious atmosphere among the teachers; find out what are the obstacles faced by teachers in teaching; routinely involving teachers in various development potentials of teachers; always motivating teachers in the form of rewards or punishments. (3) It is found that there are comfort and enthusiasm for the work of the teachers in carrying out their daily tasks of teaching and educating in the madrasah.